2019
DOI: 10.3389/fneur.2019.00826
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Responsiveness of Gait Variables to Rehabilitation Training in Parkinson's Disease

Abstract: Background: Gait disorders represent one of the most disabling features of Parkinson's disease, which may benefit from rehabilitation. No consistent evidence exists about which gait biomechanical factors can be modified by rehabilitation and which clinical characteristic can predict rehabilitation-induced improvements. Objectives: The aims of the study were as follows: (i) to recognize the gait parameters modifiable by a short-term rehabilitation program; (ii) to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…In the confirmatory analysis, the combination of both knee and trunk rotation RoMs, as the numerical sum of knee and trunk rotation angles, showed a good ability to discriminate PwPD from HCs, with a cumulative threshold value of ≤ 66.23° ( Table 3 ). Knee and trunk rotation RoM abnormalities characterize the gait pattern of PwPD, as found in the current study ( Table 1 ) and in previous studies [ 53 58 ], which also revealed a series of other kinematic gait abnormalities. Our findings indicate an ANN algorithm resulted in a drastic reduction in the amount of redundant information, allowing a focus on a few meaningful features that could be used to diagnose and monitor gait function in PwPD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the confirmatory analysis, the combination of both knee and trunk rotation RoMs, as the numerical sum of knee and trunk rotation angles, showed a good ability to discriminate PwPD from HCs, with a cumulative threshold value of ≤ 66.23° ( Table 3 ). Knee and trunk rotation RoM abnormalities characterize the gait pattern of PwPD, as found in the current study ( Table 1 ) and in previous studies [ 53 58 ], which also revealed a series of other kinematic gait abnormalities. Our findings indicate an ANN algorithm resulted in a drastic reduction in the amount of redundant information, allowing a focus on a few meaningful features that could be used to diagnose and monitor gait function in PwPD.…”
Section: Discussionsupporting
confidence: 88%
“…Reduced trunk motion combined with postural abnormalities can greatly alter the role of the spine in balance maintenance [ 6 , 68 , 75 78 ], ultimately predisposing patients to falls [ 71 ]. Notably, a recent study showed that trunk rotation is a predictor of gait recovery after rehabilitation [ 57 ], suggesting that rehabilitation should focus on recovering trunk control [ 79 , 80 ] to improve both gait and balance [ 56 58 ]. Altogether, these findings underline the importance of considering trunk kinematic abnormalities as an integral part of the gait deficit in PwPD.…”
Section: Discussionmentioning
confidence: 99%
“…This method can avoid confusion due to step changes caused by the asymmetry between the left and right sides in PD [ 24 ]. The symmetry of gait parameters was assessed through the asymmetry index (AI) (Equation ( 3 )) [ 25 27 ]. …”
Section: Methodsmentioning
confidence: 99%
“… 29 , 30 The clinical symptoms of PD are often asymmetric, and this asymmetry has also been confirmed in previous studies. 22 , 31 , 32 In the symmetry analysis of the MPS group, no difference was found in any of those parameters which indicates that MPS group still remains a symmetrical gait pattern. This finding is consistent with the clinical manifestations of MPS because the clinical symptom evaluation of these participants does not exhibit a difference between the left and right sides.…”
Section: Discussionmentioning
confidence: 88%
“…19 The asymmetry index (AI) was used to assess the symmetry of gait parameters (Formula (3)). [20][21][22] Formula (1): CV separate = SD ÷ mean value…”
Section: Resultsmentioning
confidence: 99%